Identity and Sequence Diversity of Begomovirus Associated with Yellow Leaf Curl Disease of Tomato in Indonesia - TRI JOKO SANTOSO; SRI HENDRASTUTI HIDAYAT; ATI SRI DURIAT; MUHAMMAD HERMAN; . SUDARSONO (Microbiology Indonesia, 2008)
Infection of tomato by Begomovirus is known to cause serious disease and yield losses. Samples of tomato plants showing typical symptoms of begomovirus infection were collected from eight locations in Java and Sumatra. Amplification of a putative AV1 gene was performed using AV1 specific primers for Geminivirus, total nucleic acid isolated from tomato samples exhibiting leaf curl disease as the template, and the PCR technique. Direct sequencing of PCR product was carried out, followed by nucleotide and predicted amino acid sequence analysis using the BLAST program. Positive results were obtained, the PCR amplification proved that diseased tomato samples collected from eight locations in Java and Sumatra were infected with Begomovirus. When nucleic acid and amino acid sequences of the eight isolates were compared to other begomovirus’s sequences present in the GenBank it was found that the isolates determined in this research were Indonesian isolates of AYVV. Further phylogenetic analysis of eight Begomovirus isolates identified in this study indicated they belonged into two different clades. Results of this research also suggest that the existence of Begomovirus genetic diversity in various regions in Indonesia needs further investigation. Moreover, the prevalence of distinct Begomovirus species or isolates also need investigation.